2020
DOI: 10.3390/ijerph17051688
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Training Adaptations of Endurance Performance during Combined Strength and Endurance Training in a 6-Month Crisis Management Operation

Abstract: Decreases in aerobic fitness during military operations have been observed in several studies. Thus, differences in training adaptations during a 6-month crisis-management operation were compared by using the change in endurance performance as the outcome measure. Sixty-six male soldiers volunteered for the study, consisting of pre–post assessments of blood biomarkers, body composition, physical performance, and the military simulation test (MST) performance. Physical training volume was self-reported. After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…It must be taken into consideration that higher (.3 times•wk 21 ) endurance training frequency and volume, especially with high overall training volume, may have a negative influence on strength performance outcomes during concurrent training (38,46). In the present study, no interference effect on strength development was observed, but a weak correlation between increased strength training in relation to endurance training and increased 3000-m time was found in a previous study consisting of the same study sample (32). Similarly, a relationship between higher strength training frequency and increased 3000-m time was found with linear regression analyses in the present study.…”
Section: Discussionsupporting
confidence: 59%
“…It must be taken into consideration that higher (.3 times•wk 21 ) endurance training frequency and volume, especially with high overall training volume, may have a negative influence on strength performance outcomes during concurrent training (38,46). In the present study, no interference effect on strength development was observed, but a weak correlation between increased strength training in relation to endurance training and increased 3000-m time was found in a previous study consisting of the same study sample (32). Similarly, a relationship between higher strength training frequency and increased 3000-m time was found with linear regression analyses in the present study.…”
Section: Discussionsupporting
confidence: 59%
“…Burley et al showed that following 12 weeks of Australian Army BT, recruits in the lowest performance quartiles on four different fitness tests (20 m multistage fitness test, 2 min push-up test, 1 repetition maximum box lift and 3.2 km load carriage) showed the largest improvements compared with those in the highest baseline fitness quartile 13. Similarly, Pihlainen et al reported that during 24–52 weeks of conscripted Finnish military service, performance on four different fitness tests (12 min run, standing long jump, 1 min push-up and 1 min sit-up) improved in recruits in the lowest two baseline fitness quartiles in all tests, while performance decreased in recruits in the highest fitness quartile 14…”
Section: Introductionmentioning
confidence: 87%
“…Recent studies have reported individual or subgroup changes by different levels of physical fitness at the start of military training 12–14. Burley et al showed that following 12 weeks of Australian Army BT, recruits in the lowest performance quartiles on four different fitness tests (20 m multistage fitness test, 2 min push-up test, 1 repetition maximum box lift and 3.2 km load carriage) showed the largest improvements compared with those in the highest baseline fitness quartile 13.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the research, the performance of the training period of fewer than six months is still low because it is not used to the training being undertaken. 20 The difference in value (∆) for the decrease in MDA levels increased aerobic capacity in the whey protein group. Decreased malondialdehyde levels can also be triggered by the higher content of BCAAs, such as leucine, valine, isoleucine compared to other protein products.65 Whey protein is easily digested so that it has the characteristics of increasing the ability to stimulate muscle protein synthesis and repair skeletal tissue.…”
Section: Discussionmentioning
confidence: 97%